Metal-organic framework promoting high-solids enzymatic hydrolysis of untreated corncob residues. (January 2022) - Zheng, Tianran; Yang, Luan; Ding, Meili; Huang, Chen; Yao, Jianfeng
Graphical abstract: Highlights: Adding MOFs is an easy and efficient strategy to boost fermentable sugars yield. A high hydrolysis yield of 71.47% was achieved by adding UiO-66-NH2 . Adding MOFs decreased about 50% enzyme dosage in the saccharification of CRs. Role of MOFs in improving enzymatic hydrolysis of CRs is discussed. UiO-66-NH2 is a satisfactory carrier to immobilize free cellulase. Abstract: Metal-organic frameworks (MOFs) could serve as efficient matrixes to immobilize cellulase because of their high stability and porous morphology. Herein, the Zr-based MOFs (UiO-66 and UiO-66-NH2 ) assisted 20 wt% high-solids hydrolysis of untreated corncob residues (CRs) at low enzyme loading was investigated. Glucan hydrolysis yields increased to 60.55% and 71.47% by separately adding 4 g/L UiO-66 and UiO-66-NH2 at 5 FPU/g-glucan cellulase dosage. The maximum hydrolysis yield reached 90.01% at 10 FPU/g-glucan in the presence of 4 g/L UiO-66-NH2 . Analysis of free protein concentration and cellulase activity suggested that MOFs effectively increased cellulase catalytic activity and stability, thus boosted CRs enzymatic hydrolysis efficiency. Additionally, UiO-66-NH2 immobilization gave a high catalytic activity because of the abundant anchor sites of NH2 groups. This research presents the promising future of MOFs' application in lignocellulosic biomass bioconversion and other areas requiring immobilized enzymes.